Web-Based Village Administration Service Model in Tanete Village, Simbang District, Maros Regency - Nahiruddin Nahiruddin (Jurnal Office, 2022)
The implementation of public services is an effort by the state to fulfill the basic needs of the rights of every citizen to goods, services, and administrative services provided by public service providers. Administrative services in Tanete Village, Simbang District, Maros Regency are still using the conventional system or manual system. This study aims to produce a website-based information system development model for integrated village administration services with the community and Tanete village officials. The methodology used in the study begins with data collection consisting of observation and identification, surveys, interviews and discussions with village officials. Next with the stage of developing an information system. Data was collected by means of observation, survey and document analysis. The information system development stage is carried out at the information system development stage by system analysis and system design. The results of the research are in the form of a web-based program prototype, namely the right technology to provide information on managing integrated village administration services with the community and Tanete village officials. The application makes it easier for the community and village officials to provide village administrative services.